Comparison of Corrosion Behavior of WE43 and AZ80 Alloys in NaCl and Na2SO4 Solutions - Chenxu Li; Yuming Zhao; Jinhui Liu; Jilei Xu; Dong Guo; Huanghua Zhang; Xianghong Zhou; Peixu Yang; Shaojun Zhang (Crystals, 2023)
The corrosion behavior and corrosion resistance of WE43 and AZ80 immersed in NaCl and Na2SO4 solutions were investigated, respectively. Two alloys were immersed in 0.6 M NaCl and Na2SO4 solution to observe the corrosion morphologies. Hydrogen evolution and weight loss experiments were conducted to obtain the corrosion rates. Electrochemical tests were used to characterized detailed corrosion situation. The results show that, when immersed in Na2SO4 solution, WE43 alloy shows a unique micro-galvanic corrosion behavior. On the other hand, the corrosion rate of WE43 in Na2SO4 solution is much faster than that in NaCl solution, which is the direct opposite of AZ80 and most magnesium alloys. The protection of the surface film maybe the key factor to the unexpected phenomena.